2020
DOI: 10.1007/s10787-020-00742-2
|View full text |Cite
|
Sign up to set email alerts
|

Salt-dependent hypertension and inflammation: targeting the gut–brain axis and the immune system with Brazilian green propolis

Abstract: Systemic arterial hypertension (SAH) is a major health problem around the world and its development has been associated with exceeding salt consumption by the modern society. The mechanisms by which salt consumption increase blood pressure (BP) involve several homeostatic systems but many details have not yet been fully elucidated. Evidences accumulated over the last 60 decades raised the involvement of the immune system in the hypertension development and opened a range of possibilities for new therapeutic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 156 publications
(221 reference statements)
0
12
0
Order By: Relevance
“…Contrary to our findings, experimental studies have shown the antihypertensive effects of propolis. Angiotensin-converting enzyme inhibitor-like effect, diuretic effects, activation of nitric oxide pathway, acetylcholine-induced vasodilation, and the antioxidant and anti-inflammatory properties of propolis are among the suggested mechanisms 12 , 26 , 34 40 . The vasorelaxant effects of propolis also occur as a result of inhibitory action on calcium movements through smooth muscle cells membrane 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, experimental studies have shown the antihypertensive effects of propolis. Angiotensin-converting enzyme inhibitor-like effect, diuretic effects, activation of nitric oxide pathway, acetylcholine-induced vasodilation, and the antioxidant and anti-inflammatory properties of propolis are among the suggested mechanisms 12 , 26 , 34 40 . The vasorelaxant effects of propolis also occur as a result of inhibitory action on calcium movements through smooth muscle cells membrane 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Propolis, also known as bee glue, has previously been reported to exhibit pharmacological actions, including cardioprotective effects [ 15 ]. Propolis contains a variety of active ingredients, among which flavonoids are the most biologically active components [ 14 ]. Prior work has shown that FP can attenuate pathological cardiac hypertrophy and collagen deposition in isoproterenol-treated mice through inhibition of the PI3K/AKT signaling pathway [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a dietary supplement derived from a resinous hive product collected by honeybees from various exudates of trees and plants [ 13 ]. Propolis has been shown to possess protective effects against hypertension [ 14 ] and atherosclerosis [ 15 ]. Flavonoids are major functional components of propolis, which have a long history of therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to its effect on BP, gut microbiota is associated with hypertensive target organ damage, for example, kidney and brain damage. 6,7 One study found that the changes in the intestinal microflora induced intestinal immunological gene expression and gut permeability and gut bacteria translocation into the kidney. 8 The gut and kidneys play an important role in regulating BP.…”
Section: Impact Statementmentioning
confidence: 99%